Providing free maternal health care: ten lessons from an evaluation of the national delivery exemption policy in Ghana - Sophie Witter; Sam Adjei; Margaret Armar‐Klemesu; Wendy Graham (2009)
Background: There is a growing movement, globally and in the Africa region, to reduce financial barriers to health care generally, but with particular emphasis on high priority services and vulnerable groups.Objective: This article reports on the experience of implementing a national policy to exempt women from paying for delivery care in public, mission and private health facilities in Ghana.Design: Using data from a complex evaluation which was carried out in 2005–2006, lessons are drawn which can inform other countries starting or planning to implement similar service-based exemption policies.Results: On the positive side, the experience of Ghana suggests that delivery exemptions can be effective and cost-effective, and that despite being universal in application, they can benefit the poor. However, certain 'negative' lessons are also drawn from the Ghana case study, particularly on the need for adequate funding, and for strong institutional ownership. It is also important to monitor the financial transfers which reach households, to ensure that providers are passing on benefits in full, while being adequately reimbursed themselves for their loss of revenue. Careful consideration should also be given to staff motivation and the role of different providers, as well as quality of care constraints, when designing the exemptions policy. All of this should be supported by a proactive approach to monitoring and evaluation.Conclusion: The recent movement towards making delivery care free to all women is a bold and timely action which is supported by evidence from within and beyond Ghana. However, the potential for this to translate into reduced mortality for mothers and babies fundamentally depends on the effectiveness of its implementation.